2018
DOI: 10.1002/slct.201802112
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Antifungal Potential of Carbohydrate‐Tethered Triazoles as CYP450 Inhibitors

Abstract: In search of potent and novel antifungal agents, herein, the authors report the synthesis, chemical characterization and biological evaluation of triazole tethered glycoconjugates. The structural verification of the molecules was carried out by 13C NMR, 1H NMR and mass spectra analysis. The in vitro antifungal activity was investigated against three filamentous fungi, Trichoderma viride 4329, Aspergillus fumigatus 3007 and Sporothrix schenckii. Among the synthesized compounds, it was observed that compound 10f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…All the synthesized compounds were evaluated for their in vitro antifungal activity against Aspergillus fumigates 3007 and C. albicans 3018. For A. fumigatus 3007 the growth inhibiting effect was quantitatively determined by the ratio of diameter of the growth zone in the plate with the synthesized compounds to those with the plate without the compounds (control) (Deswal et al, 2020; Nainwal et al, 2018). The plates were monitored for 96 h. While analyzing the antifungal effect, it was observed that all the compounds inhibited the fungal growth but with variable degree (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…All the synthesized compounds were evaluated for their in vitro antifungal activity against Aspergillus fumigates 3007 and C. albicans 3018. For A. fumigatus 3007 the growth inhibiting effect was quantitatively determined by the ratio of diameter of the growth zone in the plate with the synthesized compounds to those with the plate without the compounds (control) (Deswal et al, 2020; Nainwal et al, 2018). The plates were monitored for 96 h. While analyzing the antifungal effect, it was observed that all the compounds inhibited the fungal growth but with variable degree (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…A and B were used as reference compounds because they are natural ligands in the crystalline state of 5fl4 and 4iwz. The Ligprep module of the molecular modelling platform of the Schro ¨dinger Suite (Schro ¨dinger, 2022) was then used to prepare the imported structures by assigning bond lengths, bond angles, generating possible ionization states at pH 7 using Epik and finally to optimize using the OPLS4 force field (Nainwal et al, 2018).…”
Section: Docking Studiesmentioning
confidence: 99%
“…All the synthesized compounds were evaluated for their in vitro antifungal activity against Aspergillus fumigates 3007 and Candida albicans 3018. For A.fumigatus 3007 the growth inhibiting effect was quantitatively determined by the ratio of diameter of the growth zone in the plate with the synthesized compounds to those with the plate without the compounds (control) (27,28).…”
Section: Fluorescence Studymentioning
confidence: 99%